LAS OFICINAS DE RELACIONES INTERNACIONALES EN EL PROCESO DE INTERNACIONALIZACIÓN DE LA EDUCACIÓN SUPERIOR. UN ANÁLISIS A TRAVÉS DE VARIABLES DE GESTIÓN - María Julieta Abba (Universidade Federal de Santa Catarina, 2015)
In historical terms, it is considered that the international dimension of universities was there since the creation of these institutions. However, only in the last two decades has taken a new direction in a context of increasing globalization, in which higher education institutions are no longer conceived in isolation, but there are some cases of intitutions interconnected to each other overcoming geographical barriers. Therefore, in recent years it is noticed an increase in the participation of universities in the process of Internationalization of Higher Education through the creation of institutional spaces dedicated to its international linkages. In this context, the work aims to address the management of International Relations Offices of the Argentine National Universities, through a comparative case study of two large universities (Universidad Nacional de Buenos Aires y Universidad Nacional de La Plata), two medians universities (Universidad Nacional del Centro de la Provincia de Buenos Aires y Universidad Nacional de Mar del Plata), and two small universities (Universidad Nacional de Tres de Febrero y Universidad Nacional de San Martín). The research was developped through an analysis of six variables of internationalization management, implemented by the International Relationship Office, and its linkage to the size and trajectory of the institutions in which they are found. The selected variables are the strategic planning; the management of programs and projects; the evaluation and monitoring processes; the political decision of the university authorities; the professionalization and training of personnel working in the office and, finally, the linking research management process.